Everyday Life in Austerity Family, Friends and Intimate Relations - Hall, Sarah Marie (Palgrave Macmillan Studies in Family and Intimate Life,, 2019)
This book is about the impact of austerity in and on everyday life, based on a two-year ethnography with families and communities in 'Argleton', Greater Manchester, UK. Focused on family, friends and intimate relations, and their intersections, the book develops a relational approach to everyday austerity. It reveals how austerity is a deeply personal and social condition, with impacts that spread across and between everyday relationships, spaces and temporal perspectives. It demonstrates how austerity is lived and felt on the ground, with distinctly uneven socio-economic consequences. Furthermore, everyday relationships are subject to change and continuity in times of austerity. Austerity also has lasting impacts on personal and shared experiences, both in terms of day-to-day practices and the lifecourses people imagine themselves living.